Preparation in Special Education of psychologists, through the comparison between Cuba and Mali - Ahmadou Maiga (Revista MENDIVE, 2022)
Facing the current challenges which are nowadays even worse due to COVID-19, the relationship between science, technology and innovation is the base of social impacts so that the local and human development. Such a premise holds the achievement of Sustainable Development Objectives which are content into 2030 Agenda. For all the graduates at Cuban universities who are in Mali, a comparison between the contributions of both countries is a starting point to take a scientific position and for contributing to the country where they live. Coming from this necessity, this work was done and its objective is to reflect about differences and common elements between the Special Education in Mali and Cuba, so that the roll of Psychology Specialty in the process of contributing to the human development and the social transformation needed for the diversity attention. The qualitative investigation was sustained in theoretical and empirics methods based on an autobiographic narrative design. As a result, it was found that since there are no teacher training programs in Special Education in Mali, the study plan of the Bachelor of Psychology in Mali encourages intentionally influencing the educational attention to diversity.